Experimental studies on flexural action of RC beams made with hybrid rebars - A brief review - Chandra S.K. Sai; Hemalatha K.; Reddy V. Mallikarjuna; Nadh Vandanapu Swamy (E3S Web of Conferences, 2023)
Reinforced Steel bars used in concrete constructions are particularly susceptible to corrosion since they don't have enough corrosion resistance, which decreases durability and long-term performance. The main cause of steel bar corrosion is moisture interaction, which results in rust, which causes cracks and spalling, which affects durability and long-term performance. FRP bars, which have several benefits over steel bars such as strong resistance to corrosion, higher tensile strength than steel bars, and a 1/4th of the weight of steel bars, which decreases shipping and labor costs, are now entering the market as a solution to the aforementioned issues. Polypropylene fibers in concrete have high mechanical strength, stiffness, and durability. This paper tells about the type of FRP bar and Fiber that has been chosen in order to enhance the studies on the performance of flexure of RC beams made with a combination of FRP and Steel bars. From previous studies, it has been concluded that 0.25% of fibers are used as optimum dosage in terms of volume fraction in order to improve the behavior of flexure and ductility of beams made with a combination of Steel and FRP bars.